1987
DOI: 10.1002/lsm.1900070315
|View full text |Cite
|
Sign up to set email alerts
|

Laser smoke effect on the bronchial system

Abstract: The photoresection of endobronchial tumors produces smoke which is partly inhaled by the patient as well as the surgical staff. In an animal study we investigated whether a single exposure or repetitive exposures to smoke might have harmful side effects on the airways. Eleven sheep were exposed to smoke produced by laser-vaporizing (6,500 J) sections of bronchial tissue (1 cm3) in a Plexiglas chamber. The smoke analysis revealed 0.92 mg/liter particles with a mean particle size of 0.54 micron. Carbon monoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Other laboratory studies have demonstrated that smoke from both electrocautery and laser surgery is mutagenic to certain strains of Salmonella typhimurium (16,17). Animal studies have shown that repeated exposure to high levels of surgical smoke can induce inflammatory pulmonary changes, including emphysema and bronchiolitis (18)(19)(20)(21). Despite these laboratory and animal data, there are no population-based studies available to suggest whether or not repeated exposure to surgical smoke can induce carcinogenesis or chronic inflammation in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratory studies have demonstrated that smoke from both electrocautery and laser surgery is mutagenic to certain strains of Salmonella typhimurium (16,17). Animal studies have shown that repeated exposure to high levels of surgical smoke can induce inflammatory pulmonary changes, including emphysema and bronchiolitis (18)(19)(20)(21). Despite these laboratory and animal data, there are no population-based studies available to suggest whether or not repeated exposure to surgical smoke can induce carcinogenesis or chronic inflammation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory and animal studies indicate that surgical smoke has mutagenic potential and can induce inflammatory pulmonary changes in animals after repeated exposure (16)(17)(18)(19)(20)(21). On the basis of an in vitro assay, Tomita et al (16) estimated that the smoke produced during laser irradiation or electrocauterization of 1 gram of tissue is equivalent to three to six cigarettes in mutagenic potential.…”
mentioning
confidence: 99%
“…Two studies on animals revealed decreased ciliary action and increased inflammatory responses in the lungs (Freitag, Chapman, Sielczak, Ahmed, & Russin, 1987) as well as histological lung changes (Wenig, Stenson, Wenig, & Tracey, 1993). Other studies have reported similarities between surgical smoke and the adverse effects of air pollution and passive cigarette smoke (Barrett & Garber, 2003;Brüske-Hohlfeld et al, 2008;Ulmer, 2008;Weston et al, 2009).…”
Section: Research On the Risk Of Exposure To Surgical Smokementioning
confidence: 96%
“…Surgical smoke showed mutagenicity in Salmonella. Freitag, et al 1987 Eleven sheep were exposed to surgical smoke for 3 ten minute exposures to identify changes in lung function.…”
Section: Cautery Co2 Lasermentioning
confidence: 99%
“…Inhalations of these toxic aerosols have been found to be potentially damaging to the respiratory system. 18,19 Ablation of the infectious tissue poses an even …”
Section: Respiratory/environmental Hazardsmentioning
confidence: 99%